St. Kitts and Nevis : Third Review Under the Stand-By Arrangement, Financing Assurances Review and Request for Waivers of Applicability-Staff Report and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2012)
Economic activity is estimated to have softened below program expectations in January-March 2012, due to a continued contraction in the construction sector which dominated a relatively strong outturn in tourism. Despite this growth underperformance and the continued global uncertainty, the authorities have successfully implemented their home-grown economic program. While the outlook is for a moderate economic recovery, uncertain external conditions continue to present downside risks to growth.